First Report of Leaf Blight of Maize (Zea Mays L.) Caused by Exserohilum Rostratum in Tanzania - Onwunali, M. R. O.; Mabagala, R. B. (European Journal of Applied Sciences, 2022)
Maize is a popular crop and stable food in the Highlands of Tanzania. In the growing seasons of 2012 and 2013, leaf blight caused by Exserohilum rostratum was found for the first time in Ismani village, in Iringa Region. Imani village is located at S07° 27. 463ʹ, E035° 48. 231ʹ, and 1270 to 1284 meter above sea level altitude. Morphological characteristics of the pathogen showed that the conidia were cylindrical, rounded at the two ends, brown, smooth with two distinct septation, with conspicuous protruding hilum at one end of the conidia with average size of 56-128 × 11-18 μm. Conidiophores were solitary, flexuous and geniculate. Pathogenicity test revealed that inoculum density of 1.0 × 105 conidia/ml showed apparent symptoms within 48 hrs. of inoculation, and caused widespread necrosis. Exserohilum rostratum therefore could have potential effect on maize and humans in Ismani village, and possibly spread to other agro-ecological zones. This is the first report of the E. rostratum on maize foliage in Tanzania. Therefore, molecular characterization is needed to variation among Helminthosporum species pathogens of maize.